2017
DOI: 10.1002/pon.4549
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of stress coping and depression among patients with head and neck cancer: A Japanese cross‐sectional study

Abstract: This study indicates that patients with a dependent-coping pattern may account for the largest HNC population and are likely to suffer from depression. Dependent coping includes smoking, drinking, seeking support, or engaging self-distraction. In the future, we should develop psychological intervention programs focused on coping strategies and enhancement of the support system for patients with HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[ 34 ] Therefore, the result of this research is not only in line with the view of Lazarus's and Folkman's Stress and Coping Theory, but also similar to the results of previous studies. [ 35 , 36 ] Through correlation analysis, we found that coping style had the greatest impact on anxiety dimension ( r = -0.395, P < .01), followed by stress dimension. Psychoanalysis School believes that the individuals will generate anxiety emotion when encountering stressful events without taking appropriate coping styles.…”
Section: Discussionmentioning
confidence: 94%
“…[ 34 ] Therefore, the result of this research is not only in line with the view of Lazarus's and Folkman's Stress and Coping Theory, but also similar to the results of previous studies. [ 35 , 36 ] Through correlation analysis, we found that coping style had the greatest impact on anxiety dimension ( r = -0.395, P < .01), followed by stress dimension. Psychoanalysis School believes that the individuals will generate anxiety emotion when encountering stressful events without taking appropriate coping styles.…”
Section: Discussionmentioning
confidence: 94%
“…First, participants of this study could not improve their motivation for acquisition of stress coping skill during this program, though many HNC patients desire face to face sessions, providing coping strategies ( Richardson, Morton, & Broadbent, 2015 ). Our past study indicated that HNC patients commonly use the dependent coping strategy including smoking, drinking, seeking support, or engaging self-distraction ( Ichikura et al, 2018 ). The HNC patients in our study also may depend on someone or something, and may not take the initiative in dealing with stress coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have confirmed that stress coping was independent risk factor for depression in HNC patients ( Ichikura et al, 2018 , Morris et al, 2018 ). Individual psychotherapy focused on problem-solving and stress management can contribute to depression reduction for survivors of HNC in practice ( Kilbourn et al, 2013 , Semple et al, 2009 ).…”
mentioning
confidence: 88%
“…Another showed that older patients tended to use a “resigned” coping style (versus dependent or problem-focused). The dependent-coping pattern, which includes smoking, drinking, seeking support and engaging self-distraction, was found to be the most common style and was also the most likely to be associated with depression ( 189 ).…”
Section: Psychosocial Distressmentioning
confidence: 99%